Compartmentalized Neuronal Culture for Viral Transport Research - Wang, Yimin; Wang, Shan; Wu, Hongxia; Liu, Xinxin; Ma, Jinyou; Khan, Muhammad Akram; Riaz, Aayesha; Wang, Lei; Qiu, Hua-ji; Sun, Yuan (Frontiers in Microbiology, 2020)
Neuron-invading viruses usually enter via the peripheral organs/tissues of their mammalian hosts and are transported to the neurons. Virus trafficking is critical for transport or spread within the nervous system. Primary culture of neurons is a valuable and indispensable method for neurobiological research, allowing researchers to investigate basic mechanisms of diverse neuronal functions as well as retrograde and anterograde virus transport in neuronal axons. Primary ganglion sensory neurons from mice can be cultured in a compartmentalized culture device, which allows spatial fluidic separation of cell bodies and distal axons. These neurons serve as an important model for investigating the transport of viruses between the neuronal soma and distal axons. Alphaherpesviruses are fascinating and important human and animal pathogens, they replicate and establish lifelong latent infection in the peripheral nervous system, the mechanism of the viral transport along the axon is the key to understand the virus spread in the nervous system. In this review, we briefly introduce and evaluate the most frequently used compartmentalization tools in viral transport research, with particular emphasis on alphaherpesviruses.